Multiaxial fatigue of aluminium friction stir welded joints: preliminary results - D. G. Hattingh; M. N. James; L. Susmel; R. Tovo (Fracture and Structural Integrity)
The aim of the present research is to check the accuracy of the Modified Wöhler Curve Method (MWCM) in estimating the fatigue strength of friction stir (FS) welded tubular joints of Al 6082-T6 subjected to in-phase and out-of-phase multiaxial fatigue loading. The welded samples being investigated were manufactured by equipping an MTS I-STIR process development system with a retracting tool that was specifically designed and optimised for this purpose. These specimens were tested under proportional and non-proportional tension and torsion, the effect of non-zero mean stresses being also investigated. The validation exercise carried out by using the generated experimental results allowed us to prove that the MWCM (applied in terms of nominal stresses) is highly accurate in predicting the fatigue strength of the tested FS welded joints, its usage resulting in estimates falling with the uniaxial and torsional calibration scatter bands.